Relationship between teaching competence and knowledge sharing behavior in MARA Professional Colleges in Malaysia. - Abdul Hamid, Jamaliah; Sulaiman, Sarinah (2011)
This study examines teachers’ knowledge sharing behavior (KSB) and how it is related to their teaching competence. Employing a quantitative survey, data was collected from 150 teachers of MARA Professional Colleges in Malaysia. Teaching competence was found to be strongly related to KSB. Two teaching competence sub-factors appeared to be significant in predicting KSB: competence in planning and preparation, and competence in instructional delivery. The results also revealed that teachers mostly shared knowledge-content types of knowledge but their choice of mode of knowledge sharing appeared mixed.